Effect of the hormone therapy on the nutritional status and body composition of women aged 30-64 years with BMI > 25 - Pachocka, Lucyna Małgorzata; Kąpiński, Jakub Leszek (Menopause Review/Przegląd Menopauzalny, 2011)
A comparative analysis of diet and nutritional status of 183 women aged 30-64 years taking the hormone therapy and the control group taking no hormones was performed. Material and methods : Patients were divided into two groups: a group receiving hormones (HRT – 54 women) and a control group not receiving hormones (K – 129 women). The diet was assessed by interview concerning the last 24 hours. Anthropometric measurements were carried out in accordance with the WHO guidelines, while body composition was assessed by bioelectrical impedance (BIA). Results : We found a statistically significant higher percentage of lean body mass in women with HRT and not statistically significant lower body weight, BMI and waist and hips. In this group of women, a significantly higher intake of riboflavin, folate, and a smaller percentage share of energy from carbohydrates were found. Conclusions: Results of the survey indicate a beneficial effect of the hormone therapy on the body composition and basic anthropometric measurements.